Beberapa Aliran Filsafat dan Kaitannya dengan Pendidikan di Indonesia - L. Hendrowibowo (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
Education in Indonesia relates to some theories of philosophy: idealism in the context of character building and human nature, realism in the context of human commitment to the social environment, humanism relating to moral building, and pragmatism focusing on natural and social environment. The curriculum, educational content, and educational goal in Indonesia seem to be an inseparable unity. The educational effort is aimed at improving all aspects of national personality and fulfilling the need for the balanced physical, psychological, and spiritual needs. Therefore, an integrated curriculum which involves the spirit of patriotism, skill education, and professional education should be implemented.